Inequality in the Promised Land: Race, resources, and suburban schooling - Uddin, Muhammad Sharif (Journal of Interdisciplinary Studies in Education, 2020)
Inequality in the promised land: Race, resources, and suburban schooling is a well-written book by L’ Heureux Lewis-McCoy. The book is based on Lewis-McCoy’s doctoral dissertation, that included an ethnographic study in a suburban area named Rolling Acres in the Midwestern United States. Lewis-McCoy studied the relationship between families and those families’ relationships with schools. Through this study, the author explored how invisible inequality and racism in an affluent suburban area became the barrier for racial and economically minority students to grow up academically. Lewis-McCoy also discovered the hope of the minority community for raising their children for a better future.